GANGGUAN KESEIMBANGAN AIR DAN NATRIUM SERTA PEMERIKSAAN OSMOLALITAS - Rambert, Glady I. (Jurnal Biomedik : JBM, 2014)
Abstract: Water distribution in each compartment of the body involves concentration of solutes in body fluids, and the amount of dissolved substance in a solvent called osmolality. Electrolyte that has the biggest contributor in determining the serum osmolality is sodium, which is osmotically active. Hipoosmolality actually describes the state of hyponatremia, and hyperosmolality describes the state of hypernatremia. Examination of plasma and urine osmolality is very helpful in the management of patients with water and electrolyte imbalance, in addition to assess the antidiuretic hormone (ADH) abnormalities. Urine osmolality is important in evaluating the ability of the kidney to concentrate the urine, in addition to monitor the fluid and electrolyte balance. There are two ways of osmolality examination: 1) indirectly, by using osmometer (osmolality measurement) with a freezing point depression method; 2) directly, by using a formula (osmolality count).Keywords: water, sodium, osmolality, freezing point depression, osmolality countAbstrak: Distribusi air pada setiap kompartemen tubuh melibatkan kadar zat terlarut di dalam cairan tubuh, dan jumlah zat terlarut dalam suatu pelarut yang disebut osmolalitas. Elektrolit pemberi kontribusi terbesar dalam menentukan besarnya osmolalitas serum ialah natrium, yang aktif secara osmotik. Keadaan hipoosmolalitas sebenarnya menggambarkan keadaan hiponatremia, sebaliknya hiperosmolalitas menggambarkan keadaan hipernatremia. Pemeriksaan osmolalitas plasma dan urin sangat membantu penatalaksanaan pasien dengan gangguan keseimbangan air dan elektrolit, selain menilai kelainan antidiuretic hormone (ADH). Osmolalitas urin penting untuk mengetahui kemampuan ginjal memekatkan urin, selain memonitor keseimbangan cairan dan elektrolit. Terdapat dua cara pemeriksaan osmolalitas yaitu: 1) secara tidak langsung menggunakan osmometer (osmolalitas ukur) dengan metode freezing point depression; 2) secara langsung dengan menggunakan rumus (osmolalitas hitung).Kata kunci: air, natrium, osmolalitas, freezing point depression, osmolalitas hitung